Liem Sioe Liong dan Soeharto: Bisnis Tepung Terigu dan Kekuasaan di Indonesia (1966–1998) - Tjim, Gita Margareta; Sunarti, Linda; Nasirin, Anas Anwar (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2025)
The power of the New Order government regime for 32 years, led by Suharto, in the process also played a monopoly on the flour business controlled by Liem Sioe Liong through PT Bogasari Flour Mill. Liem is a Chinese businessman who has a close relationship with Suharto. The privilege given by the government to Bulog since 1972 as the sole importer of wheat. The privilege of Liem from the government is the monopoly of milling and marketing flour in the country by PT Bogasari Flour Mill. The process has created a semi-presidential patronage business network between Suharto and Liem. This study uses historical methods, which include the stages of heuristic, verification, interpretation and historiography, using the approach of economic political concepts. The results of the study found that Suharto and Liem's relations had been established since the period of the struggle for Indonesian independence, and that relationship became an economic and political structure that continued, especially during the New Order reign. PT. Bogasari Flour Mill, which controls 80% of the marketing of flour in the country, has seen a fall in all shares of PT. Prima to PT. Berdikari in 1982, and the presence of the Indomie brand instant noodles produced by PT. Indofood in 1984 increased the sentiment of exclusivity and derivative monopoly against the Salim Group and the people closest to Suharto. In July 1997, the monetary crisis that befell Thailand had an impact that spread to Indonesia. In 1998, it became the lowest point that caused the collapse of Suharto's power, which had an impact on the fall of several businesses owned by Salim Group.